Telaah Konsep Tasawuf Syeikh Yusuf Khatar Muhammad dalam Kitab Mausu’ah Yusufiyyah fi Bayani al Adilati as Sufiyyah - Ridha, Arif (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2021)
Sufism is a pure teaching originating from the Islamic religion, with roots in the Al-Qur'an and the hadith of the Prophet Muhammad SAW. This teaching emphasizes spiritual experience, the search for love, and the pleasure of Allah. Scholars agree that Sufism is an additional dimension in Islam that strengthens the personal relationship with Allah. The first scholar to be named